2000
DOI: 10.1007/pl00013675
|View full text |Cite
|
Sign up to set email alerts
|

A relativistic quark model for mesons with an instanton-induced interaction

Abstract: We present new results of a relativistic quark model based on the Bethe-Salpeter equation in its instantaneous approximation. Assuming a linearly rising confinement potential with an appropriate spinorial structure in Dirac space and adopting a residual interaction based on instanton effects, we can compute masses of the light mesons up to highest observed angular momenta with a natural solution of the UA(1) problem. The calculated ground states masses and the radial excitations describe the experimental resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 28 publications
7
94
1
Order By: Relevance
“…Relativistic corrections to interquark potentials have been provided in Refs. [18,128,129], whilst attempts at formulating a covariant picture have been made for mesons [130,131] and baryons [132][133][134].…”
Section: The Quark Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Relativistic corrections to interquark potentials have been provided in Refs. [18,128,129], whilst attempts at formulating a covariant picture have been made for mesons [130,131] and baryons [132][133][134].…”
Section: The Quark Modelmentioning
confidence: 99%
“…A study of the reliability of this type of approximation can be found in [335]. In addition to the reduction, the fully dressed quark propagators of the internal constituents are replaced by their tree-level counterparts which, instead of the current quarks in the Lagrangian, depend on large constituent-quark masses as model parameters [130,[132][133][134]336]. The purpose of such a scheme is twofold.…”
Section: Approximations and Truncationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained here are consistent with the fit of Maiani et al Now that the properties of the diquark cluster are determined, it is possible to construct a four-quark provided that the quark dynamics in hadrons is known. There exist many works which address internal quark dynamics [2,3,7,57,58,59,60,61,62,63]. Unfortunately, there is no one approach directly from QCD-a very difficult task.…”
Section: Diquark Four-quark States and New Observations By Besmentioning
confidence: 99%
“…The hyperfine interactions between quarks H hyp , as stated in [1], can be mediated by one gluon exchange, Goldstone boson exchange, or induced by the instanton interaction. The forms of these three types of hyperfine interactions in the three-quark system are explicitly given in the literature: [7,[23][24][25][26][27][28][29][30] . Those in the five-quark system with the quantum numbers of the Ω resonances were explicitly discussed in [1] and will not be repeated here.…”
Section: A Diagonal Terms Of the Hamiltonianmentioning
confidence: 99%